A diagnosis of warm-core and cold-core extratropical cyclone development using the Zwack–Okossi equation - Azad, Roohollah; Sorteberg, Asgeir (Atmospheric Science Letters, 2009)
In this study, the development of a warm-core and cold-core extratropical cyclone over North Atlantic is examined. The geostrophic relative vorticity tendency used to diagnose the development is calculated utilizing the so-called extended form of the Zwack–Okossi development equation. In both cases, the cyclonic vorticity advection acted to develop the system, but warm-air advection (diabatic heating) made the largest contribution to explosive development in the cold-core (warm-core) case. Further, a vertical cross section of the temperature advection in the warm-core case reveals that the largest values of this contributor are located far and ahead of the cyclone center. publishedVersion